2019
DOI: 10.26444/aaem/103871
|View full text |Cite
|
Sign up to set email alerts
|

Scale and forms of domestic violence against schoolchildren in rural, rural-urban and urban areas

Abstract: Introduction.In 2017, the third cyclical study on the scale of domestic violence against schoolchildren and youth in one of the rural communes of the Western Pomerania (Poland) was carried out. The study took into account five forms of violence: mental, physical, neglect, economic and sexual. The previous two editions of the study covered urban-rural (2016) and urban communities (2015). Materials and method. The research concept was implemented by means of the representative research method, using an auditing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
5
1
1
Order By: Relevance
“…Although Table 3 implies that physical violence was more prevalent among female respondents, the comparison test showed no significant difference between male and female adolescent victims ( p > 0.05). This outcome is different from a previous study that signalled a higher prevalence of physical violence among males, which suggests a greater social tolerance for physical violence among men [ 43 ]. We do not think this finding alone can prove that the cities and municipalities in this study have gender inequitable societies, since this would require further investigation [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although Table 3 implies that physical violence was more prevalent among female respondents, the comparison test showed no significant difference between male and female adolescent victims ( p > 0.05). This outcome is different from a previous study that signalled a higher prevalence of physical violence among males, which suggests a greater social tolerance for physical violence among men [ 43 ]. We do not think this finding alone can prove that the cities and municipalities in this study have gender inequitable societies, since this would require further investigation [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the share of respondents who experienced physical violence in municipalities was higher than that in cities. This is in line with research in Ethiopia, but different from studies in other sub-Saharan countries and in Poland, which demonstrated a greater likelihood of urban adolescents engaging in violence than those in rural areas [ 41 43 ]. The suggestion from a previous study [ 13 ] that the prevalence of physical violence declines with age among adolescents is also supported by our results; we found that respondents in middle school (45.3%) experienced more physical violence than those in high school (32.9%).…”
Section: Discussionsupporting
confidence: 76%
“…A fairly recent report based on three consecutive surveys conducted in Poland, another post-communist country in Central Europe, estimated the prevalence of physical violence among schoolchildren as follows: in rural areas 17.1%; in urban-rural areas 20.7%; in urban areas 29.4% ( 19 ). More specifically, acts of physical violence expressed in the form of single or repeated slapping with the hand and/or kicking, and the like, were reported by 11.3% of respondents from the rural community (2017 survey); in the urban-rural community it was 19.7% (2016 survey); whereas in the urban community it was 24.2% (2015 survey) ( 19 ). In our study, we did not observe any significant urban-rural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Although found in all three communities, negligence had a greater impact on the urban community due to the perpetration of behaviors associated with ignoring feelings and emotions, a lack of concern for the problems of children and adolescents, and the underestimation of children's illnesses. Finally, economic violence and sexual assault were perpetrated in all three types of communities (Terelak et al 2019).…”
Section: Contextual Issues As Risk Factors For the Occurrence Of Chil...mentioning
confidence: 97%
“…This climate of violence, concentrated in the family nucleus, affected around 14% of the rural, 12% of the urban-rural and 24% of the urban community. Psychological violence was predominant; physical violence was the second most common in the urban-rural community and the third most common in the urban community (Terelak et al 2019).…”
Section: Contextual Issues As Risk Factors For the Occurrence Of Chil...mentioning
confidence: 98%